'Making' as a catalyst for reflective practice. Issue 2 (4th March 2017) - Sator, Andrea J.; Bullock, Shawn M.
Abstract: Within the research and teaching program of maker pedagogy(TM), this study analyzes how teacher candidates construct knowledge about teaching and teaching with technology. The study applies an experiential-intuitive framework of reflective practice and takes cues from critical thinking to analyze the participants' interactions in a maker pedagogy lab. Schön's conception of reflection drove the data collection and analysis of participants who were asked to reflect on their experiences gained in the maker pedagogy lab. The researchers argue that the maker pedagogy lab provides participants with a way to understand their teaching practice. The results demonstrate that the maker projects enabled teacher candidates to engage in exploratory and hypothetical talk about how they are thinking about teaching and learning, particularly with technology. Furthermore, the researchers uncovered that teacher candidates' prior knowledge and frames of reference affect their making experiences and their developing identities as science and technology teachers.